El derecho comparado de la causalidad aquiliana - Infantino, Marta (2014)
this article analyzes the causal element of torts from the perspective of comparative law, focusing on the field of tort liability. Thus, it specifies both the particular aspects of the investigation as well as each legal system studied. then, the article discusses the differences and similarities of each system. Later, it stops on the dominant approaches examining its success on facing the tort phenomenon in order to highlight the essential characteristics that determine the various approaches tort liability can assume.